教師在知識翻新環境之跨領域教學設計對GAI的提問與感知研究 - 曾莉婷(Li-Ting Tseng); 陳美如(Mei-Ju Chen); 翁暄睿(Hsuan-Jui Weng) (Jiao yu yu xin li yan jiu, 2024)
Traditional teacher education focuses on single subjects, limits interdisciplinary knowledge, hinders communication and collaboration, and reduces confidence in interdisciplinary teaching design. Generative AI (GAI)’s vast databases can compensate for teachers’ limited interdisciplinary knowledge, but the quality of its output relies on effective prompting (or questioning, hereafter referred to as prompting). The collaboration between teachers and GAI in interdisciplinary teaching design makes effective prompting essential, highlighting the need for a Knowledge-Building environment that fosters collaboration and idea development. This study focuses on 18 in-service teachers and explores how they engage in interdisciplinary teaching design within a Knowledge- Building environment integrated with GAI. A mixed-method approach was used to analyze their prompting progress and perceptions of GAI. The study found that: (1) Teachers’ prompting behavior with GAI primarily focused on extracting and inferring informatio